Internet of things support for marketing activities. (17th February 2020) - Taylor, Mark; Reilly, Denis; Wren, Chris
ABSTRACT: Internet-enabled consumer devices are to be developed by the manufacturers. In this article, we examine how the Internet of things (IoT) can support marketing activities, including customer relationship management, business intelligence, and product design. In particular, the research reported in this article examines how the IoT can provide communication channels to support targeted marketing for product owners and enhance customer relationship management and product support. In addition, in this article, we examine how data gained from the operational use of Internet-enabled devices can support business intelligence in terms of how consumers actually use a product and can also support new product design in terms what features of current Internet-enabled products are most commonly used and how they are used.